THE USE OF DEIXIS IN THE NOVEL "THE FIVE PEOPLE YOU MEET IN HEAVEN" BY MITCH ALBOM - Utami, Narissa; Nur, Sahril (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
This study explores the application of deixis in Mitch Albom's novel The Five People You Meet in Heaven. Deixis is a part of pragmatics that discusses the context in an utterance. The purpose of this study is to find out the types of deixis used in the novel and to analyze the function of the deixis found in the novel The Five People You Meet in Heaven. In analyzing deixis, this study uses Yule's theory (1996) which divides deixis into three categories: person deixis, spatial deixis, and temporal deixis. Person deixis is used to show people, spatial deixis is used to show location, and temporal deixis is used to show time. This study belongs to a qualitative research with descriptive qualitative because the data is obtained in the form of words or utterances. In collecting the data, this study uses the documentation method which is carried out through note-taking and reading strategies. The results showed that there are three types of deixis found in the novel The Five People You Meet in Heaven. They are person deixis, spatial deixis, and temporal deixis. There were a total of 888 deixis data found. Among them are 800 person deixis, including 368 first person deixis, 305 second person deixis, and 127 third person deixis. Meanwhile, there are 59 spatial deixis data and 29 temporal deixis data. Each deixis has a different function depending on the context of the utterance. The person deixis found among others functions as subject, object, possessive adjective, possessive pronoun, and reflexive pronoun. Meanwhile, the spatial deixis found functions as an adverb of place because it indicates a certain location based on the context of the utterance. In addition, the temporal deixis found functions as an adverb of time indicating past, present, and future time.